0123 Reconstruction of individual radiation doses in a cohort of french nuclear workers: considering doses under the recording threshold. (21st August 2017) - Fournier, Lucie; Laurier, Dominique; Caër-Lorho, Sylvaine; Samson, Eric; Leuraud, Klervi
Abstract : Context: The French nuclear worker cohort enables the evaluation of potential health effects of protracted low doses of ionising radiation. Dosimeters worn by the workers record annual individual exposure. However, below a certain value called recording threshold, dose quantification is too imprecise to be recorded and the dose is then considered to be null. This study aims to evaluate the magnitude of doses below the recording threshold with regards to the recorded doses. Methods: The cohort includes 59 004 workers, hired from 1950 and followed-up until 2004. A comprehensive review of the dosimetry practices in the facilities participating in the study was performed. Data on recording thresholds, minimal detectable levels and dosimeter reading frequencies was collected and analysed. Scenarios based on monthly data were used to impute doses under the threshold. Results: Recording threshold doses and reading frequencies decreased substantially over the cohort's follow-up period (from 0.5 to 0.2 milliSievert and from bimonthly to quarterly respectively) but the annual percentage of null recorded doses increased (from 51% to 91%). Results from the imputation of below the threshold doses will be presented. Conclusion: The estimation of doses under the threshold is complex, needs a precise reconstruction of the monitoring history, and requires modelling assumptions. Preliminary results indicate that the availability of monthly data plays a crucial role in evaluating the magnitude of doses under the recording threshold. Declaration of potential conflict of interest: : The work under consideration gets into the general framework of a research program with shared financial support by IRSN, AREVA and EDF.